Histopatology kidney of seed white snipper (lates calcarifer bloch) which experienced a different decrease in salinity - Larasati Putri Hapsari (JURNAL PERIKANAN DAN KELAUTAN, 2022)
White snapper (Lates calcarifer Bloch) is a consumption fish that has high economic and nutritional value. FAO stated that white snapper was a diversified species in aquaculture in 2018. This is because white snapper has many advantages such as fast growth rate, high fecundity, easy hatchery techniques in controlled containers, and high adaptability to various environmental conditions. The method used in this study was experimental with a completely randomized design (CRD) technique using 3 treatments with each treatment being repeated 3 times. The 3 treatments include; A : Water medium with a salinity content of 5 ppt; B : Water medium with a salinity content of 10 ppt; C : Water media with 15 ppt salinity. In this study, white snapper seeds measuring ±3 cm were given 3 different salinity treatments. The three treatments, salinity 5 ppt, 10 ppt, and 15 ppt caused histopathological abnormalities in the kidneys of snapper fish which were used as research objects. The kidney organ has Melano Macrophages Centers (MMC) and Necrosis (N). Kidneys with MMC are characterized by the presence of inflamed organ parts and a collection of pigmented macrophages. The occurrence of necrosis is characterized by the loss of tissue structure and then the kidney tissue is damaged, as well as the loss of cell boundaries or cell nuclei.